Celestina’s Erasmian Turn: Feliciano de Silva’s Sequel - Romero, Loreto (Revista Canadiense de Estudios Hispánicos, 2023)
In 1534 Feliciano de Silva published Segunda Celestina, the first and most influential of several sequels of Fernando de Rojas’s editorial hit. In this entertaining and light-hearted fiction, Silva brings the old bawd back to life and reinvents the original story to rectify its erotic and violent atrocities with the moral truths of the faith as envisioned by Erasmus’s Christian humanist thinking, which transpires in the spiritual, social, and ethical values comprised in the text. This essay explores the ways in which Segunda Celestina, in dialog with Erasmus’s ideas, portrays, in a jovial and rather carnivalesque manner, the spiritual progress of a morally imperfect, but inherently virtuous society. In this light, Segunda Celestina can be construed as Silva’s attempt to write a book of entertainment for a popular audience that would also be profitable from a humanist and Christian standpoint.